Identification of a novel potential antitumor activity of gossypol as an APE1/Ref-1 inhibitor - Qian CY; Li MX; Sui JD; Ren T; Li Z; Zhang L; Zhou LW; Cheng Y; Wang D (Dove Medical Press, 2014)
Chengyuan Qian, Mengxia Li, Jiangdong Sui, Tao Ren, Zheng Li, Liang Zhang, Liwei Zhou, Yi Cheng, Dong WangCancer Center, Daping Hospital and Research Institute of Surgery, Third Military Medical University, Chongqing, People's Republic of ChinaAbstract: The human apurinic/apyrimidinic endonuclease 1/redox enhancing factor-1 (APE1/Ref-1), an essential multifunctional protein involved in the repair of oxidative deoxyribonucleic acid (DNA) damage and transcriptional regulation, is often overexpressed in tumor tissues and cancer cells. Moreover, APE1/Ref-1 (APE1) overexpression has been linked to chemoresistance in human tumors. Thus, inhibiting APE1 function in cancer cells is considered a promising strategy to overcome resistance to therapeutic agents. Gossypol is a Bcl-2 homology 3 (BH3)-mimetic agent and is able to bind to the BH3 domain of B-cell lymphoma 2 (Bcl-2) family members. Other studies demonstrated that Bcl-2 directly interacted with APE1 via its BH domains. Using apurinic/apyrimidinic (AP) endonuclease assays, we found that gossypol inhibits the repair activity of APE1. Electrophoretic mobility shift assays and dual luciferase assays showed that gossypol could also inhibit the redox function of APE1. Using dual polarization interferometry technology, we show that gossypol can directly interact with APE1. Furthermore, addition of gossypol, in conjunction with APE1 overexpression, leads to cancer cell death. The addition of gossypol also enhances the cell killing effect of the laboratory alkylating agent methyl methanesulfonate and the clinical agent cisplatin (DDP). Administration of gossypol significantly inhibited the growth of xenografts. Furthermore, the combined treatment of gossypol and DDP resulted in a statistically higher antitumor activity compared with DDP alone in vivo. In conclusion, we have demonstrated that gossypol effectively inhibits the repair and redox activity of APE1 through a direct interaction.Keywords: cancer, oxidative DNA damage, BH3-mimetic